Changes in antioxidant enzymes and growth parameters in rice (Oryza sativa L.) genotypes under submergence - Damanik, Revandy Iskandar Muda (2013)
Submergence is one of the main abiotic stresses limitations for yield and quality production of many important crops. In order to better understand the physiological and biochemical responses by submergence stress in rice (Oryza sativa L.), this thesis was mainly examined to clarify the biochemical markers of contrasting rice genotypes/cultivar during cell level, germination and seedling stages, and discusses the basis of tolerance related genotypes /cultivar. For that reason, in order to recognize and also understand better for the biochemical mechanism of submergence tolerance,the objective of this study was to find out the activities of antioxidant enzymes (superoxide dismutase, SOD; catalase, CAT; ascorbate peroxidase, APX; glutathione reductase, GR), as well as for lipid peroxidation in rice plant subjected to different periods of submergence stress. The isoenzymic profile analysis of the antioxidant enzymes also examined in anoxia-stressed suspension culture to get further understanding of the mobilization of protein reserves as well as apperearance of new isoenzymes in submergence stress. Until now, there have been some researchs and reports related to the influence of submergence stress on the growth of rice plants at seedling growth (Colmer and Pedersen, 2008; Das et al., 2005; Ella et al., 2003; Sarkar et al., 2001), but only a small amount of research has been focused on the influence of submergence stress at early stage (a week after germination) of seedling. Plant growth rate and antioxidative defense responses of early seedlings in six selected Malaysian rice genotypes, MR84,MR185, MR219, MR219-4, MR220, and MR219-9, and FR13A cultivar (known as cultivated plant for submergence tolerant) at different submergence periods (4, 8, and 12 days) were examined. Eleven day old seedlings of hypoxia resistant Malaysian rice genotypes and tolerant rice cultivar (FR13A) were hydroponically grown in normoxic or hypoxic conditions inside the laboratorium. The result on chlorophyll content in rice seedlings suggested that photosynthesis was affected beginning as early as 4 d under submerged condition, except for FR13A cultivar. Activities of superoxide dismutase (SOD) increased linearly with the longer periods of submergence stress until up to 8 d submerged for FR13A cultivar, and MR84, MR185, MR219-4, and MR219-9 genotypes when compared with the control. In contrast, the result showed that catalase (CAT) activity was activated while ascorbate peroxidase (APX) activity was deactivated, and vice versa, in response for submergence conditions for FR13A cultivar and MR219-9 genotype. Additionally, submergence stress led to a significant increase in glutathione reductase (GR) activity for all genotypes started at 4 d to 8 d after being submerged, except for MR219 genotype. From the results obtained in this study, give strength to our hypothesis that detoxification of O2 _ to H2O2 was maintained at a stable level throughout the submergence stress until up to 8 days (specifically for MR219-4 and MR219-9 genotypes) and the role of GR might be more efficient in cytotoxic H2O2 necessary for the observed protection from submergence stress. The potential involvement of activated oxygen species by submergence stress was studied also focusing on two Malaysian rice genotypes, MR219-4 and MR219-9, and cultivar FR13A at the seedling stages. Fourteen-day-old seedlings of three rice cultivars were subjected to different submergence periods (4, 8 and 12 days) in greenhouse. Under 8 days of complete submergence, FR13A cultivar showed higher lipid peroxidation in terms of malondialdehyde (MDA) level and activities of antioxidative enzymes, superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), and glutathione reductase (GR) when compared to the MR219-4 and MR219-9 genotypes. MR219-9 genotype showed higher SOD, APX and GR activities after 12 days of submergence. The levels of SOD activity indicated that detoxification of O2.- to H2O2 was maintained at a stable level throughout the submergence stress until up to 8 days and increased rapidly at 12 days of submergence. The results showed that tolerance to submergence is linked until 8 days submergence for MR219-4 genotype and FR13A cultivar. In addition, CAT activity has much higher affinity for scavenges H2O2 than APX, therefore ascorbate glutathione cycle might be more efficient to scavenge H2O2. The consequence of oxygen deprivation (anoxia) on the antioxidant system in suspension culture of anoxia intolerant Malaysian rice genotypes and FR13A genotype cells was examined. The antioxidative enzymes were decreased for MR219-4 and MR219-9 genotypes for CAT and APX activities, and increased in FR13A cultivar starting at 20 days in suspension culture compared to that of control. CAT and APX activities were maintained higher in oxygen depriviation conditions for all genotypes and cultivar suggested that anoxia stress in suspension cultures induced the level of H2O2 to toxic levels. The relationship between the enzyme activity and isoenzyme of the SOD and peroxidase (POD) in cell suspension rice submitted to anoxia stress (oxygen depriviation) has been evaluated. Cell suspension culture of rice exhibited three kinds of SOD bands, identified as MnSOD, FeSOD and Cu/ZnSOD. A substantial improvement was identified in the activity of MnSOD isozymes since it has been prominent appeared for all genotypes and cultivar at different periods of stress. It is practical to take on that mitochondrial partition senses oxygen depletion condition faster than the rest of the cell (peroxisome, chloroplast, etc) partition because it is the most important consume of oxygen. The higher activity of POD and its isoenzymes activities for MR219-4 genotype and FR13A cultivar, maybe compensate for the decline in CAT activity. These results recommend that POD, SOD and CAT activities play necessary and synergy protection responsibility aligned with H2O2 toxic levels in rice suspension culture in anoxia condition. Induction of their isoenzymes/isoforms and activities of POD, CAT and SOD provide protection from oxidative damage,hence these parameters might be taken as selection criteria for study of submergent tolerance in rice.